2022
DOI: 10.3390/medicina58020325
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Common Femoral Artery and Vein: Anatomical Morphology, Vessel Relationship, and Factors Affecting Vessel Size

Abstract: Background and Objectives: We aimed to analyze the morphology of the common femoral artery (CFA) and common femoral vein (CFV) and the anatomical relationship between the two blood vessels, and to investigate the factors that influence the size of these blood vessels. Materials and Methods: This retrospective study included 584 patients who underwent abdominal and pelvic computed tomography from 1 February to 28 February 2021. We measured the vessels at three regions on both lower extremities (inguinal ligamen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Some have suggested that this may be due to differences in arterial caliber in women and men. In a recent report analyzing femoral artery size on contrast-enhanced CT scans of the abdomen, male sex was significantly associated with a larger common femoral artery size [61]. The risk of bleeding and/or vascular complications is especially concerning in patients with AMI-CS where large bore vascular access is needed.…”
Section: Bleeding and Vascular Complicationsmentioning
confidence: 99%
“…Some have suggested that this may be due to differences in arterial caliber in women and men. In a recent report analyzing femoral artery size on contrast-enhanced CT scans of the abdomen, male sex was significantly associated with a larger common femoral artery size [61]. The risk of bleeding and/or vascular complications is especially concerning in patients with AMI-CS where large bore vascular access is needed.…”
Section: Bleeding and Vascular Complicationsmentioning
confidence: 99%